Correlation between Reading Comprehension and Writing Coherence in Junior High EFL Learners - yani, Ida; Bafadal, Moh Fawzi; Hiadayati, Hidayati; Ilham, Ilham (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the correlation between reading comprehension and writing coherence among English language learners in junior high school. This study used a quantitative approach with a correlational design to determine the correlation between reading and writing. 17 eighth grade students from MTs Raudatul Jannah were selected through purposive sampling. Data were obtained using a standardized reading comprehension test and an analytic rubric that assessed coherence in students' written texts. Pearson correlation analysis showed a moderate positive correlation (r = 0.63, p 0.05) between students' reading comprehension scores and the coherence of their writing. This finding suggests that higher reading comprehension is associated with greater coherence in writing. This study highlights the pedagogical implication that integrated reading and writing instruction can improve students' overall language performance in an EFL environment.